2003
DOI: 10.1177/106480460301100103
|View full text |Cite
|
Sign up to set email alerts
|

Human-Centered Design of Unmanned Aerial Vehicles

Abstract: Technology advances and increased application of UAVs will demand greater attention to human factors concerns in design, deployment, and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Along that line, Mouloua et al (2003) have indicated that operator vigilance and target search/recognition capabilities are key elements to be considered for human-centered design in UAV control. For example, consider the detection and engagement of hostile aircraft in the vicinity of a UAV, a situation proposed by Thompson (2000) as a future concept of operations.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Along that line, Mouloua et al (2003) have indicated that operator vigilance and target search/recognition capabilities are key elements to be considered for human-centered design in UAV control. For example, consider the detection and engagement of hostile aircraft in the vicinity of a UAV, a situation proposed by Thompson (2000) as a future concept of operations.…”
mentioning
confidence: 98%
“…They also eliminate the risk of pilot fatalities and have generally lower aircraft operating costs. Consequently, UAVs are expected to have an increasing role in current and future aviation (Mouloua, Gilson, & Hancock, 2003).…”
mentioning
confidence: 99%
“…By 2015, at least five major automobile manufacturers plan on incorporating systems designed to monitor headway error, track and avoid collisions, and adaptively maintain a set cruise speed (Walker, Stanton, & Young, 2001). Increasing automation of functions previously performed by human drivers is also integral to Future Combat Systems such as armed robotic vehicles, recovery and maintenance vehicles, intelligent munitions systems and unmanned air vehicles (Mouloua, Gilson, & Hancock, 2003).…”
Section: The Influence Of Automation On Performancementioning
confidence: 99%
“…The level of training and experience as well as support by backup personnel and equipment can only raise these limitations to a certain extent [2]. These considerations lead to the question how a UAV system can support the operator adequately in mission planning and execution and how its resilience against the effects of data link loss and human cognitive limitations can be raised.…”
Section: Introductionmentioning
confidence: 97%